KONSEP ÊMBAT DALAM KARAWITAN JAWA - Sri Hastanto (LP2M ISBI Bandung, 2012)
Êmbat is one of the musical concept in Javanese gamelan music – karawitan Jawa. It is a kind of musical characteristic of a gamelan ensamble which is generated by its interval structure – Jv. jangkah – of that gamelan. The only way to understand êmbat, one may investigate gamelan tuning system. Êmbat had been metioned in old Javanese manuscripts including Centhini and Wédhapradangga. Kunst and Hood also discussed êmbat in some extend, but the result does not quite fit to reality. This work aims to explain the concept of êmbat from the angle of the culture owner – Javanese.In order to explain the concept, this study has firstly to discover the concept of pitch in karawitan Jawa, secondly the tolerance of the limit in sifting tones , and finally approaching the main goal: the concept of êmbat it self. To reach the goal this studi conducted some simple experiments. Key words:structure of jangkah, tolerance of sifting notes, and êmbat